2018
DOI: 10.1029/2018gl078662
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intraseasonal Oscillations in SMAP Salinity in the Bay of Bengal

Abstract: Analysis of Soil Moisture Active Passive (SMAP) mission derived sea surface salinity (SSS) during April 2015 to December 2017 in the Bay of Bengal (BoB) shows first revelation of new insight of existence of 30‐ to 90‐day and 10‐ to 20‐day period Intraseasonal Oscillations (ISOs) in SSS—all phase‐locked during August–December. The seasonal SMAP SSS anomaly (SSSA) minimum (−0.5 to −1.0 practical salinity unit, psu) occurs in October and exhibits year‐to‐year variation, while SSSA maximum (0.5 psu) occurs in June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…The Aquarius products' signals remain the lowest in amplitude among the available salinity satellites but spatially consistent with previous MJO studies on the order of ±0.1 psu (Grunseich et al, ; Li et al, ). The oscillatory response of SMAP SSS to MJO forcing is on the order of ±0.2 psu and consistent with Subrahmanyam et al (). SMOS exhibits a similar response to SMAP at ±0.2 psu in the Hovmöller and spatial figures (Figures and ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The Aquarius products' signals remain the lowest in amplitude among the available salinity satellites but spatially consistent with previous MJO studies on the order of ±0.1 psu (Grunseich et al, ; Li et al, ). The oscillatory response of SMAP SSS to MJO forcing is on the order of ±0.2 psu and consistent with Subrahmanyam et al (). SMOS exhibits a similar response to SMAP at ±0.2 psu in the Hovmöller and spatial figures (Figures and ).…”
Section: Resultssupporting
confidence: 89%
“…Studying SSS variability during MJO propagation will allow for a better understanding of air‐sea interaction associated with the MJO, especially due to technological advancements of the past decades transitioning from spatially scarce in situ methods to globally expansive, high spatiotemporal resolution satellite‐derived methods. The MJO has been detected in satellite‐derived salinity from the European Space Agency's Soil Moisture Ocean Salinity (SMOS; Maes et al, ), the National Aeronautics and Space Administration (NASA)'s Aquarius/SAC‐D (Grunseich et al, ; Guan et al, ; Shinoda et al, ), and NASA's Soil Moisture Active Passive (SMAP; Subrahmanyam et al, ) missions. Similarly, comparisons of Aquarius/SAC‐D and SSS output from the HYbrid Coordinate Ocean Model have shown that both can capture near equatorial MJO‐induced SSS variability (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The high temporal resolution of satellite SSS enabled a better understanding of large-scale intra-seasonal phenomena (e.g., Subrahmanyam et al, 2018), including the Madden-Julian Oscillation (MJO) -the dominant climate mode at sub-seasonal time scales in the tropics that impacts the global weather and climate (Zhang, 2005). Satellite SSS measurements enable characterization of the SSS signature associated with MJO and the associated impacts on surface density variations (Grunseich et al, 2013;Guan et al, 2014;Li et al, 2015), emphasizing the role of upper-ocean dynamics in regulating MJO.…”
Section: Scientific Drivers For Satellite Salinity Improving Knowledgmentioning
confidence: 99%
“…SMAP is available from 2015 to present. Satellite-derived salinity has been used in several studies of the Indian Ocean but is underutilized in monsoon studies on the whole (Murty et al, 2004;Nyadjro et al, 2012;Nyadjro & Subrahmanyam, 2016;Paris & Subrahmanyam, 2018;Subrahmanyam et al, 2018).…”
Section: Data 211 Reanalysis Productsmentioning
confidence: 99%